2011
DOI: 10.1590/s0102-86502011000700013
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture attenuates liver and kidney oxidative stress in anesthetized rats

Abstract: PURPOSE:Investigate the effects of a single electroacupuncture (EA) session at acupoints Zusanli (ST-36) and Zhongwan (CV-12) combined in regulating oxidative stress in liver and kidney in anesthetized rats. METHODS: Eighteen healthy rats randomly assigned to 3 groups (n=6) were anesthetized intraperitoneally with ketamine (90mg kg -1 body weight) + xylazine (10mg/kg body weight): G-1: Control (anesthesia), G-2: anesthesia+EA10Hz and 10 mA, 10 Hz) applied to right ST-36 and CV-12 acupoints for 30 minutes. G-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…Despite the fact that is known that there is a correlation observed between the plasma levels of MDA, and the level of 17-beta estradiol where high levels of this hormone may lead to oxidative stress 27 we cannot exclude the effects of EAc on the increase in lipid peroxidation. We have reported similar results in other tissues in two previous studies [16][17] .…”
Section: U/g Ovarian Tissuesupporting
confidence: 89%
See 1 more Smart Citation
“…Despite the fact that is known that there is a correlation observed between the plasma levels of MDA, and the level of 17-beta estradiol where high levels of this hormone may lead to oxidative stress 27 we cannot exclude the effects of EAc on the increase in lipid peroxidation. We have reported similar results in other tissues in two previous studies [16][17] .…”
Section: U/g Ovarian Tissuesupporting
confidence: 89%
“…The use of EAc has promoted an increase in GSH levels in the liver and kidneys and in random skin flaps of rats, as demonstrated in previous studies [16][17] . Lipid peroxidation was more intense in rats treated with EAc as there was a significant raise in MDA levels in G3 and G4 rats.…”
Section: Discussionsupporting
confidence: 52%
“…Published studies have demonstrated the effects of Ac in attenuating oxidative stress in experimental spinal cord injury 9 and in rats in menopause 10 . Whereas previous studies have proved the attenuating effects of the EAc on the oxidative stress on liver 11 and kidneys 11 , skin 12 , and in the ovaries 3 , it is expected that protection also may occur in rats submitted to testis torsion/detorsion. No similar studies were found in the literature, hence the importance of this investigation.…”
Section: Introductionmentioning
confidence: 87%
“…In anaesthetized rats, even a single 30-min 10/100 Hz EA session could enhance lipid peroxidation and simultaneously reduce oxidative stress in liver and kidney tissue. 86 EA increases the mean blood flow or perfusion in the liver as well, 87 which may be a benefit to patients undergoing laparoscopic procedures. In endotoxaemic rats, EA at PC6 significantly attenuated elevated biochemical markers of liver and renal injury, markedly decreased the infiltration of neutrophils into liver tissues caused by LPS, and reduced the renal histopathological score.…”
Section: Lungsmentioning
confidence: 99%